2019
DOI: 10.1093/ce/zkz019
|View full text |Cite
|
Sign up to set email alerts
|

A polyoxometalate redox flow battery: functionality and upscale

Abstract: While redox flow batteries carry a large potential for electricity storage, specifically for regenerative energies, the current technology-prone system—the all-vanadium redox flow battery—exhibits two major disadvantages: low energy and low power densities. Polyoxometalates have the potential to mitigate both effects. In this publication, the operation of a polyoxometalate redox flow battery was demonstrated for the polyoxoanions [SiW12O40]4– (SiW12) in the anolyte and [PV14O42]9– (PV14) in the catholyte. Emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
0
21
0
3
Order By: Relevance
“…Table 3 shows that the number of publications in recent years, since 2013, on RFBs based on POMs is very limited. With the exception of Friedl et al in 2019 [125], the remaining studies show, generally, a low cell area compared to what has been reported in VRFBs (≤5 cm 2 ). Furthermore, although there are some interesting efficiency values, the current densities are still low.…”
Section: Polyoxometalatesmentioning
confidence: 85%
See 2 more Smart Citations
“…Table 3 shows that the number of publications in recent years, since 2013, on RFBs based on POMs is very limited. With the exception of Friedl et al in 2019 [125], the remaining studies show, generally, a low cell area compared to what has been reported in VRFBs (≤5 cm 2 ). Furthermore, although there are some interesting efficiency values, the current densities are still low.…”
Section: Polyoxometalatesmentioning
confidence: 85%
“…The interaction of the redox centers of the POMs is generally reduced due to their large sizes [3] and the electrons added by reduction to the POMs are not allocated to a specific atom, therefore allowing for fast kinetics and high-power densities [122,123]. Moreover, the large size of the POMs, which range from 6 to 25Ȧ [124], along with the electrostatic repulsion, do not allow the permeation through the actual RFBs' commercial cation exchange membranes (CEM), preventing cross-over and mixing of the active species [125]. The interest in applying POMs to RFBs is vast and is still at an infant stage.…”
Section: Polyoxometalatesmentioning
confidence: 99%
See 1 more Smart Citation
“…[80] This also illustrates the advantages of using two independent electrolytes in asymmetric RFBs,a st he anolyte and catholyte can be adjusted individually to achieve an optimized whole-cell performance.I n addition, Stimming and co-workers observed by 51 VN MR spectroscopy that, upon degradation, the [PV 14 O 42 ] 9À cluster reassembled under operational conditions.T his behavior could lead to significantly longer operational lifetimes for POM-based RFBs compared to other RFB systems. [76,81] The POM/POVsystem has also recently been successfully scaledup and operated in ap ilot-scale reactor. [81] These studies demonstrate the scalability and advantages of aqueous POM/ POVRFBs.…”
Section: Povsi Nredox-flow Batteriesmentioning
confidence: 99%
“…DOI: 10.1002/adma.202005019 charge carrier behaviors, which allows POMs to display unparalleled physical and chemical properties compared to traditional metal oxides. [2] In this regard, the intrinsic charge carrier behavior of POM-based materials is undoubtedly the cornerstone for their diverse applications in molecular electronics, [20][21][22][23][24][25][26][27][28][29] solar cells, [30][31][32][33] redox flow batteries, [34][35][36][37][38][39][40][41] and molecular-cluster batteries. [42][43][44][45] The charge carrier behaviors of POM-based materials are present on two levels.…”
mentioning
confidence: 99%